Vacuum ultraviolet discharge excited lasers - Richmond, A (1987)
﻿ The thesis concerns experimental studies of discharge excited lasers operating in the vacuum ultraviolet (VUV) region of the spectrum. The known molecular fluorine laser operating at 157nm, on a bound- to-bound transition of the F2 molecule was selected for initial study. As a result of the work reported here the energy per pulse was increased by a factor of five (10mJ to 50mJ) from that of earlier F2 lasers. Similary the working lifetime of the gas mixture was increased from a few shots to several thousand by the application of cryogenic gas purification techniques. These improvements have resulted in the development of a practical commercial F2 laser. The performance characteristics of the fluorine laser and their relationship to the physical mechanisms are discussed. With the objective of achieving laser action in the 110 to 130nm region of the VUV a novel scheme is investigated. The scheme involves the production of a population inversion between the v'=1 level of the b1πu state of molecular nitrogen and high lying levels of the X1Σg ground state. The excitation of the upper laser level involves production of N2 molecules in the a1πg state by means of a pulsed discharge. Transfer of population from this intermediate 'a' state to the upper level is accomplished by absorption of radiation at 308nm from a discharge excited xenon chloride laser. The practicality of this scheme has been investigated to the extent that populations of the order of 1013 molecules per cm3 have been produced in the 'a' state and laser induced fluorescence on the 'b' to 'X' band has been observed. Under the conditions of "the present experiments the potential VUV gain is too small (10-4cm-1>/sup>) to reach laser threshold. The problems of increasing the gain to reach threshold for a practical device are discussed.